A Novel and Efficient Synthetic Route to (±)-Serinolamide A via Aziridine Ring Opening and Amide Coupling - Amardeep Ramprasad Jadhao; Adinath Devidas Badar; Pramod Shahajee Phatak; Kiran Fulchand Shelke; Jyotipal Jaiprakash Khadse; Nikhil Bhikaji Umbarkar; Santosh Babanrao Gaikwad (International Journal of Scientific Research in Chemistry, 2025)
(±)-Serinolamide A, a serinol-derived fatty acid amide, plays an important role in cannabinoid receptor modulation. While existing synthetic approaches rely on direct amidation or enzymatic coupling, we present a new, efficient and modular synthetic route utilizing selective aziridine ring opening followed by amide bond formation with fatty acid chloride. This method offers enhanced regioselectivity, scalability, and adaptability to structural analogs.
Keywords: Regeoselective; (±)Serinolamide A; Aziridine Ring Opening; Fatty acid chloride; Amide Coupling